PDCA Method Implementation to Reduce the Potential Product Defects in the Automotive Components Industry - Fredy Sumasto; Cantika Puspa Maharani; B. Handoko Purwojatmiko; Febriza Imansuri; Siti Aisyah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
The research aim to reduce the potential for product defects in the automotive component industry by implementing Plan-Do-Check-Action (PDCA). The application of the PDCA method was carried out in an automotive component manufacturing company in Indonesia which produced SLJ 91 parts as a research object. The causes of the high number of product defects are known at the Plan stage from setting the theme of improvement to the root cause by using a fishbone diagram and 5W+1H analysis. In the Do stage, system improvements are implemented from the solutions generated by the 5W+1H analysis. The repair results are controlled to confirm the results of the repairs made. The corrective actions taken resulted in a reduction in product defects of 2.8% so that they were included in the maximum tolerance for the number of defects in the SLJ 91 part. Based on the results of data processing, analysis, and comparison between before and after implementation, it was found that the defect rate for SLJ 91 products was reduced from 10.8 % to 8%, a reduction in the percentage of 2.8% so that the product reaches the quality target it should be. The results of the repair had a direct impact on the type of dent defects, namely a decrease in the number of defects from 8.6% to 5.3%, so that there was a decrease of 3.3%. The results of the research are implemented and standardized in the action stage so that the improvements made can be maintained in the long term.